Integrating pharmacogenomics- metabolomics towards realising personalised medicine for colorectal cancer patients treated with 5-fluorouracil / Hazwanie Hashim - Hashim, Hazwanie (Institute of Graduate Studies, UiTM, 2012)
Colorectal cancer (CRC) is one of the most common cancers among men and women in Malaysia. 5-flurouracil (5-FU)/leucovorin is the standard chemotherapy for colorectal cancer and various other types of cancer including breast, head and neck cancers. However, standard method for dosing 5-fluorouracil (5-FU) still lacks accuracy and reliability. In addition to the body surface area index (BSA) that is currently used in dosing regimen, other factors such as genotype, age, gender and drugdrug interaction needs to be accounted. We explore the value of pharmacogenomics and metabolomics in personalising medicine in patients treated with 5-FU. We intended to profile both the genetics and metabolomics markers that could be useful in the clinical monitoring of patients’ responses towards 5-FU and its disease. Genetic polymorphism of DPYD and UGT1A1 show interethnic differences among the populations studied. The frequency of DPYD*5, DPYD 1896 T>C, UGT1A1*28 and UGT1A1*6 was high in this study. Patients who experienced neutropenia had significantly higher serum concentration of 5-FU as compared to those who did not have it (Mann Whitney-U test, p-value= 0.031).